Researcb on Network Security Monitoring Model and Associated Algoritbm in tbe Age of Big Data - Lan Liu; Jun Lin; Jun Cai (Dianxin kexue)
In the age of big data, large-scale, complexity of heterogeneous network security behavior should be considered. According to the features of huge amount and complex, big data analysis technologies for network security monitoring were proposed. Various types of heterogeneous data sources by data cleaning, and the key data through security event correlation, traffic rules based on wavelets and distributed sequence diagram model and other methods, were analyzed. Some ideas of network security monitoring system for big data environment were provided.